Síntese de 5-seleno-1,2,3-triazóis policíclicos via reação dominó: cicloadição/selenilação mediada por sais de cobre - Teixeira, Wystan Kreisly Othon (2022)
In recent years, the number of works involving the synthesis of selenium-containing molecules has increased considerably, especially due to its pharmacological activities and potential application in materials science. Nevertheless, in spite of the considerable advances that have been made in this field, the design of general and efficient cascade strategies to construct of polycyclic [1,2,3]-triazoles, containing 1,2,3-triazole group fused to a selenium heterocycle is still not achieved. Given the importance of this class of compounds, it is extremely important the development of new and efficient methodologies that can allow obtaining these seleno-heterocycles. We herein describe a copper salt mediated interrupted click-selenylation domino reaction, to synthesize selenium cycle fused 1,2,3-triazoles in one-pot from 1,2-bis(2-azidoaryl)diselenides and terminal alkynes under microwave irradiation. The methodology offers a broad scope, proceeds well, affords the products in moderate to excellent yields, and advantageously, the reaction could be carried out by using dimethyl carbonate, an environmentally benign and sustainable solvent. Moreover, it was also demonstrated that this methodology could be successfully extended to TMS-protected alkynes as well as to bioactive alkynes. A plausible reaction mechanism has also been proposed based on the control experiments and previous reports.